The warning - Applegate, Katherine (New York : Scholastic, 1998)
Jake and the other Animorphs have discovered a Web page that discusses how to conquer the Yeerks, but before they can trust anyone they have to determine if it is for real or if it is a trap.
"An Apple paperback.".
Christian Library.
6.7
3-6
Keywords: Extraterrestrial beings -- Fiction; Good and evil -- Fiction; Science fiction; Extraterrestrial beings -- Fiction; Good and evil -- Fiction; Science fiction